Precise synthesis of pH‐responsive copolymers with naphthoic acid side groups via living cationic polymerization. Issue 24 (5th October 2013) - Shinke, Yu; Kanazawa, Arihiro; Kanaoka, Shokyoku; Aoshima, Sadahito
ABSTRACT pH‐Responsive homopolymers and copolymers with naphthoic acid side groups were synthesized via base‐assisting living cationic polymerization. To this end, the feasibility of the living cationic polymerization of ethyl 6‐[2‐(vinyloxy)ethoxy]‐2‐naphthoate (EVEN) was first examined using a base‐assisting initiating system. Et1.5AlCl1.5 as a Lewis acid catalyst induced the living cationic polymerization of EVEN in the presence of ethyl acetate or 1, 4‐dioxane in CH2Cl2 at 0 °C. In contrast, the use of naphthoxyethyl vinyl ether (NpOVE), which is a nonsubstituted counterpart, resulted in a poorly controlled polymerization under these conditions. The presence of the carboxy ester was most likely critical in preventing side reactions. A subsequent alkaline hydrolysis of the side‐chain esters quantitatively yielded a carboxy‐containing polymer. Aqueous solutions of this polymer underwent pH‐driven phase separation at pH 7.0. Well‐defined random and block copolymers were also prepared with various functional segments, and their stimuli‐responsive behaviors were investigated in terms of solution transmittance and aggregate size. Block copolymers containing two different pH‐responsive segments formed micelle‐like structures between the two phase‐separated pH values, and dual stimuli‐responsive copolymers containing a pH‐responsive polyacid segment and a thermosensitive segment self‐assembled in the water in response to both the pH and temperature. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 5239–5247